Effect of rowing posture on body measurements and skin–sportswear interface pressure and implications on garment fit. (August 2021) - Vasile, Simona; Cools, Joris; De Raeve, Alexandra; Malengier, Benny; Deruyck, Frank
Sportswear should fit well each individual athlete while preserving its ergonomic and pressure comfort upon sport-specific movements. This study aims to quantify the effect of two rowing postures on selected body measurements and skin–sportswear interface pressure for competitive rowers of age 18–35. The results based on average body measurements of a total number of 74 male and female rowers indicate a considerable influence of the catch and finish posture on both body measurements and interface skin–sportswear pressure, regardless of the gender. Back length and across back width were the most affected by posture, and increased especially from the static to catch position by 12% (6.1 cm) and 16% (6.5 cm) for male rowers, and respectively by 11% (4.9 cm) and 13% (4.7 cm) for female rowers. In general, the posture led to the larger influence on pressure than on anthropometrics of maximum 55% versus 16% for male and up to 82% versus 13% for female rowers, respectively. The maximum interface pressure (e.g. 10 mmHg) was rather low, which suggest there was no pressure discomfort. Prototypes were developed and the fit of garments was investigated in various postures. For the considered fabrics and design, an increase of the garment pattern to accommodate the catch maximum changes led to a poor fit of the prototype MR58-CP, which was generally too large, especially in the static posture. On the contrary, prototype MR58-FP that considered some finish rowing posture-related body changes and design adjustments based on experience with the first prototype and input from the test person had the best fit.